The potential cost of a failed Doha Round - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2009)
This study offers new conclusions on the economic cost of a failed Doha Round. The first section is devoted to an analysis of how trade policies evolve in the long and medium runs. We show that even under normal economic conditions, policymakers modify tariffs to cope with the evolution of world markets. We then use the MIRAGE Computable General Equilibrium model to assess the potential outcome of the Doha Round, and then examine four protectionist scenarios. Under a scenario where applied tariffs of major economies increase up to the currently bound tariff rates, we find that world trade decreases by 7.7 percent and world welfare drops by US$353 bn. We then compare a resort to protectionism when the Doha Development Agenda (DDA) is implemented versus a resort to protectionism when the DDA is not implemented. We find that this trade agreement could prevent the potential loss of US$ 809 bn of trade, and could therefore act as an efficient multilateral insurance scheme against the adverse consequences of “beggar-thy-neighbor” trade policies.